The inspection activity and the rights of the administrated: The inspection reports - Villegas Vega, Paul (2022)
By means of this article, the author explains the legal nature of the audit reports or inspection reports, detailing their evidentiary value and the manifestation of the principles of due process, material truth and legitimate exercise of power. To this end, the author starts by developing the nature of the audit activity in the Peruvian legal system and its link with the sanctioning power of the public administration, taking into account the provisions of Chapter II of Title IV on the audit activity in the General Administrative Procedure Law.